Adsorption of binary mixtures of sodium hexadecyl sulfate and ethoxylated octylphenols from aqueous solutions at activated carbon - Maksin, Victor; Kochkodan, Olga; Kovshun, Lidiya (Київський національний університет імені Тараса Шевченка, 2019)
Adsorption of binary mixtures of sodium hexadecyl sulfate and oxyethylated octylphenols surfactants from aqueous solutions at activated carbon AG-3 was studied. It is found that the process of mixed adsorption depends on total surfactants concentration in the mixture, the ratio of components in the mixture and their surface activity. Adsorption data is confirmed by measurements of the zeta potential values of activated carbon particles in the surfactants mixtures.
Keywords: adsorption; surfactant; adsorption layer; activated carbon